Perancangan Interior Panti Werdha Usia Anugerah di Surabaya - Wijaya, Nadya Allencia; Wibowo, Mariana; Frans, Stephanie Melinda (Intra, 2018)
The elderly is the final phase of human life. At this phase, human change is prominent both physically and mentally, therefore extra care is needed to improve the welfare of elderly people. Family plays an essential role in caring for the elderly and helping the elderly to reach the available resources in order to meet the needs of their life. However, due to current development in this modern era and increasing demands of life, the habits of children or families to take care of their elderly parents are decreasing rapidly. Changes within the family structure are causing the family to consider that the existence of elderly is a burden.The interior design of the Usia Anugerah Nursing Home aims to fulfill all the needs of the elderly who do not receive special attention from their family. This design uses an analytical method by conducting field observation and interviewing directly as well as interacting with the elderly to clearly know the problems occurred. The Design of the Usia Anugerah Nursing Home uses the Healing Â Environment approach in form of a garden in order to overcome hollow nest syndrome which gives negative impact on the elderly. In addition, the concept implementation of "Serve with Heart" is applied in the design in order to provide a sense of comfort and positive influence while in the nursing home.